Analyzing The Content Of The Biology Book For The Fifth Scientific Grade In The Light Of Visual Thinking Skills (Journal of the College of Basic Education, 2024)
The research aims to analyze the content of the biology textbook for the fifth scientific grade in light of visual thinking skills. This involves creating a list of visual thinking skills that should be included in the content of the biology textbook for the fifth scientific grade and assessing the extent to which these skills are present in the textbook. To achieve the research objectives, a descriptive method was employed using content analysis. The research population and sample consisted of the biology textbook prescribed for fifth scientific grade students in Iraq for the academic year 2023/2024, which comprises seven chapters containing 156 figures. The study tool was a content analysis card developed based on visual thinking skills. The key findings of the study showed the availability of visual thinking skills to varying degrees and at a low availability rate across all chapters. Based on these findings, the researcher made several recommendations, the most important of which is the need to enhance the skills of making connections, interpreting information, analyzing it, and deriving meanings more effectively in the visual elements of the biology textbook for the fifth scientific grade.